NILAI DIAGNOSTIK ANTIGEN TB DENGAN RAPID TEST DEVICE (TB AG) UNTUK TUBERKULOSIS PARU - Sri Kartika Sari; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
In Indonesia, the diagnosis of pulmonary tuberculosis relies primarily on an identification of acid-fast bacilli on sputum smears. However, microscopic device has several limitations. The sensitivity of microscopic examination is variable. The quality of smear microscopic results is heavily depend on the workload, and the skill of the technician’s reading the slide. TB antigen rapid test device (TB Ag) is fast, easy and does not either need skillness of the operator. The kit detects specific secreted antigen M.tuberculosis coded by: RD (Region of Difference) 1, RD2 and RD3. These RD1−3 were found deleted from BCG (Bacille Calmette-Guerine) vaccine strain. In the present study, the diagnostic value of TB Ag was assessed. Sputum samples were examined from 59 suspected tuberculosis patients and 22 non tuberculosis patients. The samples of the suspected tuberculosis patients were collected as three consecutive sputum specimens (spot, morning, spot). The total 199 specimens were examined by sputum smear microscopy and TB Ag. M.tuberculosis culture by using Lowenstein Jensen media, which was used as a gold standard. The sensitivity and specificity of microscopic sputum smear were 83.8% (95% CI: 70.0–89.4) and 96.3% (95% CI: 89.8–98.7), respectively. While, the sensitivity and specificity of TB Ag were 72.6% (95% CI: 63.9–79.9) and 90.9% (95% CI: 72.2–97.5), respectively. The concordance between microscopic sputum smear and TB Ag was 70.8%. TB Ag can be considered as a new diagnostic tool for the diagnosis of pulmonary tuberculosis, especially at the health services where there is no expert technician available for microscopic sputum smear examination.